Evaluasi Program Kerja Kepemimpinan Kepala Madrasah dalam Meningkatkan Mutu Pendidikan di MTs Negeri 2 Kota Bengkulu - Hendra Saputra (UIN Fatmawati Sukarno Bengkulu, 2026)
Abstrac: The purpose of this study is to describe the work program of the madrasah principal's leadership in improving the quality of education at MTsN 2 Bengkulu City. Using a descriptive qualitative method, the CIPP model approach (context, input, process and product). The results of the study indicate that the general madrasah principal's leadership work program has been good in improving the quality of education. First, the context of the madrasah principal's leadership work program has had a program, program needs, and work program objectives. Second, program input through strategic plans such as improving teacher competency, learning models/media, teacher creativity, classroom supervision, monitoring, discipline, relationships with parents, guardians and the community, supervision and guidance to teachers, working together with related elements, collaboration between educators and staff, giving rewards and punishments, awareness of responsibility among teachers, parents, guardians, and the community. Third, process. The work program has been implemented through planning outlined in the madrasah principal's strategic plan. Fourth, product. Has carried out strategic plans such as commitment, planning, and continuous implementation, encouraging changes in teachers and professional staff, taking corrective actions to achieve the vision, mission, goals, and targets of the madrasah towards superior accreditation quality. Thus, the quality of madrasa education can be improved through evaluation of the madrasa principal's leadership work program. Therefore, it can be suggested that to improve the quality of madrasa education, the evaluation of leadership work programs in madrasas should be increased.Keywords: Evaluation, Madrasah Principal Leadership Program, Quality of Education. Abstak: Tujuan penelitian ini untuk mengevaluasi program kerja kepemimpinan kepala madrasah dalam meningkatkan mutu pendidikan di MTsN 2 Kota Bengkulu. Menggunakan metode kualitatif deskriptif, pendekatan model CIPP (contex, input, proses dan produk). Hasil penelitian menunjukkan bahwa program kerja kepemimpinan kepala madrasah secara umum telah bagus dalam meningkatan mutu pendidikan. Pertama, contex program kerja kepemimpinan kepala madrasah telah ada program, kebutuhan program, dan tujuan program kerja. Kedua, input program melalui rencana strategi seperti peningkatan kompetensi guru, model/media pembelajaran, kreatifitas guru, supervisi kelas, monitoring, kedisiplinan, silaturahmi dengan orang tua, wali murid dan masyarakat, pengawasan dan bimbingan kepada guru, bekerja sama unsur terkait, kolaborasi pendidik dan staf, memberikan penghargaan dan hukuman, kesadaran tanggung jawab sesama guru, orang tua, wali murid, dan masyarakat. Ketiga, proses. Program kerja telah terlaksana melalui perencanaan dituangkan dalam rencana strategi kepala madrasah. Keempat, produk. Telah melakukan rencana strategi seperti komitmen, perencanaan, dan pelaksanaan yang berkelanjutan, mendorong perubahan profesional guru dan staf, mengambil tindakan korektif untuk mencapai visi, misi, tujuan, dan sasaran madrasah ke arah mutu akreditasi unggul. Dengan demikian, mutu pendidikan madrasah dapat ditingkat melalui evaluasi program kerja kepemimpinan kepala madrasah. Oleh karena itu dapat disarankan bahwa untuk meningkatkan mutu pendidikan madrasah, maka tingkatkanlah evaluasi program kerja kepemimpinan di madrasah. Kata kunci: Evaluasi Program Kata Kunci; Evaluasi, Program Kepimimpinan Kepala Madrasah, Mutu Pendidikan.